Smart Defense 5.0 to Strengthen the Defense of Indonesia's Capital City (IKN) - Putra, Hedriman; Winarna, Agus; Bonifasius, Bonifasius; Albrecht, Malte; Ghazalie, Ghazalie (Graduate School of Universitas Negeri Malang, 2024)
The Indonesian Capital City (IKN) relocation to IKN Nusantara automatically requires a qualified defense concept. The relevant concept to be implemented is IKN-Smart Defense 5.0, which is an approach that integrates advanced technology and innovative strategies to improve national security and resilience. This research is discussed using theories of strategy and defense strategies, a research methodology with a qualitative approach, and a collection of research and literature studies. The study results prove that IKN-Smart Defense 5.0 offers an innovative and integrated approach to facing future security challenges. This concept can improve defense capabilities and ensure national security in the digital era by utilizing advanced technology and encouraging collaboration between sectors.